Experimental Microporomechanics - Ulm, Franz Josef; Delafargue, Antoine; Constantinides, Georgios (My University, 2005)
© 2005, CISM, Udine. Is it possible to break down natural porous material systems down to a scale where materials no longer change from one material to another, and upscale (‘nanoengineer’) the behavior from the nanoscale to the macroscale of engineering applications? — This is the challenging question we address in these lecture notes through a review of tools and methods of experimental microporomechanics. The combination of advanced experimental indentation techniques and microporomechanics theory provides a unique opportunity to understand and assess nanoproperties and microstructure, as a new basis for the engineering prediction of macroscopic poromechanical properties of natural composites. This is illustrated for cement-based materials and shales.
Keywords: Indentation Depth; Indentation Modulus; Indentation Test; Interfacial Transition Zone; Orientation Distribution Function